Prediction of Tetraoxygen Reaction Mechanism with Sulfur Atom on the Singlet Potential Energy Surface - Ashraf Khademzadeh; Morteza Vahedpour; Fereshte Karami (The Scientific World Journal)
The mechanism of S+O4 (D2h) reaction has been investigated at the B3LYP/6-311+G(3df) and CCSD levels on the singlet potential energy surface. One stable complex has been found for the S+O4 (D2h) reaction, IN1, on the singlet potential energy surface. For the title reaction, we obtained four kinds of products at the B3LYP level, which have enough thermodynamic stability. The results reveal that the product P3 is spontaneous and exothermic with −188.042 and −179.147 kcal/mol in Gibbs free energy and enthalpy of reaction, respectively. Because P1 adduct is produced after passing two low energy level transition states, kinetically, it is the most favorable adduct in the 1S+1O4 (D2h) atmospheric reactions.